Sheltered Workshop Di Surakarta - Bahar, Syamsuddin, Dr. Ir. Dhani Mutiari, MT (2016)
The existence of disabled people, especially in Surakarta is still underestimated by the public and regarded as a burden for the family. The high number of unemployed disabled people due to the lack of attention from the government and society, especially in terms of employment. Therefore, it is still a bit of a public facility that is already friendly with disabilities. This resulted in the difficulty of disabled people to develop and distribute their work to market and other marketing facilities. With the problems it is need provided a container which is accessible for disabled people to sell the work at the same time honing skills in marketing in the world of work. The building sheltered workshop is a workshop employment for disabled people, equipped with a place to memarmerkan works well as a place for marketing, with the concept of building an accessible expected these buildings can be accessed easily by people with disabilities, also be a building that is beneficial for them, especially in the city of Surakarta to promote their self-reliance work.. Keywords: empowerment, disabled people, work independence.`